CONTINUOUS MIDWIFERY CARE (continuity of care) For Mrs.F WITH GRADE II BIRTH CANAL LACERATION AT PERA INDEPENDENT PRACTICE MIDWIFE MEDAN CITY IN 2024 - ingatindruru; Manik, Rikky Mangaranap TM; Pangaribuan, Ingka Kristina; Ginting, Siska Suci Triana; Sinaga, Kamelia (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Birth canal tears that occur in mothers during childbirth are a condition where the cervix is lateralized in more than half of vaginal deliveries. Most tears are less than 0.5 cm in size. Meanwhile, deep tears may extend into the upper third of the vagina. If the birth canal laceration is not treated immediately, it can cause bleeding. The purpose of this study was to apply continuous midwifery care to Mrs. F with Grade II Birth Canal Laceration at Pera independent practice midwife, Kec.Medan tuntungan, Kota medan Tahun 2024. The research method used is descriptive research. The subject of the study was Mrs. F with a second degree Perenium Tear at the Medan tuntungan independent practice midwife in 2024. The results of this study are that continuous midwifery care has been carried out on Mrs. F with Grade II birth canal laceration by providing perineal care to the mother.